Diffusivity alterations related to cognitive performance and phenylalanine levels in early-treated adults with phenylketonuria - Jèssica Pardo; Clara Capdevila-Lacasa; Bàrbara Segura; Adriana Pané; Pedro J. Moreno; Glòria Garrabou; Josep M. Grau-Junyent; Carme Junqué; Consortium PKU.cat (Journal of Neurodevelopmental Disorders)
Abstract Background Altered white matter (WM) is consistently reported in patients with phenylketonuria (PKU). However, the knowledge about WM microstructural integrity in early-treated adults with classical PKU and its relationship with cognition and metabolic parameters is inconclusive. This study aims to explore the cerebral WM microstructural alterations in adult patients with early-treated classical PKU and their association with blood phenylalanine (Phe) levels and neuropsychological performance using whole-brain diffusion tensor imaging (DTI). Methods Twenty-nine patients with early-treated classical PKU (mean age = 30.86, SD = 7.74) and 31 healthy controls (mean age = 32.45, SD = 9.40) underwent neuropsychological assessment and MRI. Phe dry blood spot (DBS-Phe) samples, along with venous Phe levels, were collected from the PKU sample to calculate the index of dietary control (IDC). Tract-based spatial statistics (TBSS) of the mean diffusivity (MD), and fractional anisotropy (FA), were carried out with FSL v6.0.4 to assess between-group differences and to explore associations with both cognitive and clinical data. Results Patients exhibited a widespread white matter tract involvement, with lower MD and higher FA values compared to controls. The most affected tracts were the inferior longitudinal fasciculus and inferior fronto-occipital fasciculus for MD, and the anterior corona radiata, uncinate fasciculus and forceps minor for FA. MD negatively correlated with IDC and venous Phe levels, whereas FA negatively correlated with full-scale intelligence quotient (FSIQ) (p-value ≤0.05 FWE-corrected). Conclusions Microstructural WM alterations were present in adults with early-treated classical PKU, and these abnormalities were related to global intelligence and metabolic control markers. Although our results suggest the importance of proper disease management, further studies are needed to determine its long-term relevance.